Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Organizational Citizenship Behaviour (OCB) Di UPT Puskesmas Teladan Medan - Ananda, Fitri Tia; Rahmani , Nur Ahmadi Bi; Aslami , Nuri (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to examine the effect of organizational culture and leadership style on organizational citizenship behavior (OCB) on employees of UPT Puskesmas Teladan Medan, either partially or simultaneously. This study uses quantitative methods with data collection using the Likert scale method. The subjects used in this study were employees of the UPT Puskesmas Teladan Medan, totaling 50 people and were taken using total sampling. Data analysis technique through IBM SPSS statistics 25 program. The results of this study indicate that first, organizational culture has a positive and significant effect on organizational citizenship behavior (OCB) with a significant value of 0.000 0.05. Second, leadership style has a positive and significant effect on organizational citizenship behavior (OCB) with a significant value of 0.001 0.05. And third, simultaneously organizational culture and leadership style have a positive and significant effect on organizational citizenship behavior (OCB) with a significant value of 0.05, which is 0.000 0.05.